Emerging trends in eating disorders among sexual and gender minorities - Nagata, Jason M; Ganson, Kyle T; Austin, S Bryn (Current opinion in psychiatry, 2020)
To review the recent literature on eating disorders, disordered eating behaviors (DEB), and body image dissatisfaction among sexual and gender minority populations, including, but not limited to, gay, lesbian, bisexual, and transgender people. Overall, eating disorders, DEB, and body dissatisfaction are common among sexual and gender minority populations. Lifetime prevalence for anorexia nervosa (1.7%), bulimia nervosa (1.3%), and binge-eating disorder (2.2%) diagnoses are higher among sexual minority adults compared with cisgender heterosexual adults in the United States. Lifetime prevalence of eating disorders by self-report of a healthcare provider's diagnosis are 10.5% for transgender men and 8.1% for transgender women in the United States, including anorexia nervosa (4.2 and 4.1%) and bulimia nervosa (3.2 and 2.9%), respectively. DEB may be perpetuated by minority stress and discrimination experienced by these individuals. Body dissatisfaction may be a core stressor experienced by transgender people; gender dysphoria treatment has been shown to increase body satisfaction. A particular clinical challenge in caring for transgender youth with eating disorders is the standard use of growth charts based on sex. Novel research demonstrates that sexual and gender minorities with eating disorders have unique concerns with regards to disordered eating and body image.